2018
DOI: 10.1155/2018/9051854
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Head and Neck Cancers: Does It Have Only One Face?

Abstract: Head and neck squamous cell cancer (HNSCC) represents a significant burden worldwide. Chemoprevention of HNSCC is a means of cancer control with a use of drugs or natural agents in order to hinder or delay the cancer development. The purpose of this article is to review mechanism of action of different chemopreventive agents' groups and results of most important researches concerning them. The safety issues of HNSCC chemoprevention are also discussed. In case of HNSCC there is currently no agent, which would g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 112 publications
0
10
0
Order By: Relevance
“…[ 34 ] Previous studies also showed elevated levels of TBARS, LHPO, and CD within the circulation of oral cancer‐bearing animals. [ 35 ] The oral administration of Vicenin‐2 drastically reduced the degree of plasma and buccal mucosa membrane TBARS in DMBA‐brushed OSCC hamsters, which indicates that Vicenin‐2 has an anti‐lipid peroxidative capability against buccal carcinogenesis. Both the enzymatic/nonenzymatic antioxidants play imperative roles in ROS‐arbitrated oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] Previous studies also showed elevated levels of TBARS, LHPO, and CD within the circulation of oral cancer‐bearing animals. [ 35 ] The oral administration of Vicenin‐2 drastically reduced the degree of plasma and buccal mucosa membrane TBARS in DMBA‐brushed OSCC hamsters, which indicates that Vicenin‐2 has an anti‐lipid peroxidative capability against buccal carcinogenesis. Both the enzymatic/nonenzymatic antioxidants play imperative roles in ROS‐arbitrated oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Green tea (camellia sinensis) contains various cancer preventive catechins which are epigallocatechin gallate (EGCG), epigallocatechin (EGC) and epicatechin gallate (ECG). It was found that drinking over 10 cups (120 mL/cup) of green tea per day could prevent cancer recurrence in various organs in humans (12,13). In 1987, the cancer preventive activity of EGCG was first reported (14), and since then, the significance of EGCG and green tea in cancer prevention and treatment has become widely recognized (15).…”
Section: Introductionmentioning
confidence: 99%
“…Physiologic doses of retinoids also stimulate killer T-cell production and cell-mediated cytotoxicity, which may be crucial in the treatment of cancer. [ 14 15 ] The teratogenic action of retinoids has been the most serious adverse effect. [ 16 ] Vitamin C: Vitamin C is the most prevalent antioxidant component of fruits and vegetables, which could exert chemopreventive effects and can prevent oxidative stress–mediated chronic diseases without apparent toxicity at doses higher than the current recommended dietary allowance of 100–120mg/day for adults.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…Physiologic doses of retinoids also stimulate killer T-cell production and cell-mediated cytotoxicity, which may be crucial in the treatment of cancer. [ 14 15 ] The teratogenic action of retinoids has been the most serious adverse effect. [ 16 ]…”
Section: Aterials and M Ethodsmentioning
confidence: 99%